THE EVALUATION OF THE LIFTING SPEED BY SQUAT METHOD ON TRUNK MUSCLES ACTIVITY : Life Science - physiology - SIAVASH, ETEMADINEZHAD.; GHOMSHE.FARHAD, TABATABAI; BAFGHI, SORAYANI; HOSSEIN YAZDANI CHARATI . JAMSHID, MOHAMMAD (International Journal of Life Science and Pharma Research, 2017)
the lifting of the loads is one of the risk factors for occupational back pain and the study of trunk muscles as the main and involved muscles in lifting is important from viewpoint of biomechanics and ergonomics. This study aimed to investigate the effect of lifting speed on the activity of lumbar and abdominal muscles during lifting by Squat method. the number of 27 healthy men was studied; so that, there was no medical history of low back pain and musculoskeletal disorders in these men. The data were collected from the left and right Erector spinae and the Multifidus muscles as well as the left and right Rectus and external oblique of the participants using electromyography (EMG); and after filtering and normalization of data to MVC, the signal processing was performed using MATLAB software. The statistical analysis was carried out using SPSS 16. the statistical analysis showed that the trunk muscles activities at high, medium and low speeds were significant (p<0.05). It also observed that the load weight which is lifting by a person has a direct effect on the activity of trunk muscles. it can be concluded that the lifting speed, in addition to the weight of load, can be considered as a risk factor for low back pain.